Picturing words: Creating illustration for a novel. Issue 1 (1st December 2012) - Smy, Pam
This article explores the visual research undertaken by an illustrator in response to a manuscript written for children by the author, Linda Newbery, published by David Fickling Books in 2010. In response to the text, the illustrator documents the variety of forms in which imagery for publication is researched and created, with emphasis on the role that the sketchbook can play as a research tool for the illustrator.